ZAT BERBAHAYA PADA MAKANAN - Lina Wati; Rika Wulandari (JURNAL ILMIAH NUSANTARA, 2025)
Makanan is one of the basic human needs that must be guaranteed in terms of safety and health. However, in reality, many foods on the market still contain hazardous substances such as formalin, borax, and textile dyes. This issue raises concerns about the long-term impacts on public health. This study aims to comprehensively examine the types of harmful substances often found in food, their health effects, and control efforts. The research uses a literature study method by collecting information from scientific journals, BPOM data, and other credible sources. The results show that harmful substances are commonly found in processed foods, school snacks, and products without official distribution permits. In addition to affecting the digestive system, prolonged consumption of these substances can lead to internal organ damage and even cancer. This study recommends the need for massive public education and strengthened government supervision to ensure better food safety in Indonesia.